RANCANG BANGUN APLIKASI SISTEM PAKAR TROUBLESHOOTING SEPEDA MOTOR HONDA BERBASIS ANDROID (Information Technology and Telematics, 2013)
Troubleshooting a Honda motorcycle damages arising problem in Honda motorcycles can be due to damage to the motor component of the core system and damage the motorcycle. This expert system design includes creating decision tables, decision trees, forward chaining method, data flow diagram (DFD) and Entity Relationship  (ERD).  created using the Java programming language and using the softwar eclipse sqlite database. The objectives are to make the system malfunction troubleshooting application android based Honda motorcycle capable of solving problems with the Honda motor impairments using a mobile phone or android-based tablet.Keywords: Troubleshooting, expert systems, Java, Eclipse, sqlite, Android.